The Basel II Risk Parameters Estimation, Validation, Stress Testing - with Applications to Loan Risk Management - Engelmann, Bernd; Rauhmeier, Robert; SpringerLink (Online service). (Berlin, Heidelberg Springer Berlin Heidelberg, 2011)
The estimation and the validation of the Basel II risk parameters PD (default probability), LGD (loss given fault), and EAD (exposure at default) is an important problem in banking practice. These parameters are used on the one hand as inputs to credit portfolio models and in loan pricing frameworks, on the other to compute regulatory capital according to the new Basel rules. This book covers the state-of-the-art in designing and validating rating systems and default probability estimations. Furthermore, it presents techniques to estimate LGD and EAD and includes a chapter on stress testing of the Basel II risk parameters. The second edition is extended by three chapters explaining how the Basel II risk parameters can be used for building a framework for risk-adjusted pricing and risk management of loans.
Statistical Methods to Develop Rating Models -- Estimation of a Rating Model for Corporate Exposures -- The Shadow Rating Approach - Experience from Banking Practice -- Estimating Probabilities of Default for Low Default Portfolios -- Transition Matrices: Properties and Estimation Methods -- A Multi-Factor Approach for Systematic Default and Recovery Risk -- Modelling Loss Given Default: A "Point in Time"-Approach -- Estimating Loss Given Default - Experiences from Banking Practice -- Possibilities of Estimating Exposures -- EAD Estimates for Facilities with Explicit Limits -- Validation of Banks' Internal Rating Systems - A Supervisory Perspective -- Measures of a Rating' s Discriminative Power - Applications and Limitations -- Statistical Approaches to PD Validation -- PD-Validation - Experience from Banking Practice -- Development of Stress Tests for Credit Portfolios -- Risk Management of Loans and Guarantees -- Risk Management of Loans with Embedded Options.
Electronic reproduction.
Keywords: Econometrics; Industrial management; Credit -- Mathematical models; Risk -- Mathematical models; Credit ratings -- Mathematical models; Electronic books